A new type of 3‐D peripheral ultrastructure in Glaucocystis (Glaucocystales, Glaucophyta) as revealed by ultra‐high voltage electron microscopy. Issue 3 (19th April 2016) - Takahashi, Toshiyuki; Nishida, Tomoki; Saito, Chieko; Yasuda, Hidehiro; Nozaki, Hisayoshi
Abstract : The coccoid glaucophyte genus Glaucocystis is characterized by having a thick cell wall, which has to date prohibited examination of the native ultrastructural features of the protoplast periphery. Recently, however, the three‐dimensional (3‐D) ultrastructure of the protoplast periphery was revealed in two divergent Glaucocystis species, with the world's most powerful ultra‐high voltage electron microscope (UHVEM). The two species exhibit morphological diversity in terms of their 3‐D ultrastructural features. However, these two types do not seem to encompass actual ultrastructural diversity in the genetically diverse genus Glaucocystis . Here, we report a new type of peripheral 3‐D ultrastructure resolved in " G. incrassata " SAG 229‐2 cells by 3‐D modeling based on UHVEM tomography using high‐pressure freezing and freeze‐substitution fixation. The plasma membrane and underlying flattened vesicles in " G. incrassata " SAG 229‐2 exhibited grooves at intervals of 200–600 nm, and the flattened vesicles often overlapped one another at the protoplast periphery. This 3‐D ultrastructure differs from those of the two types previously reported in other species of Glaucocystis . The possibility of classification of Glaucocystis species based on the 3‐D ultrastructure of the protoplast periphery is discussed.